2018
DOI: 10.21873/anticanres.12534
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose LNG-IUS as Therapy for Endometrial Hyperplasia. A Prospective Cohort Pilot Study

Abstract: Abstract. Background/Aim: Progestin therapy has been accepted as therapy for low-and medium-risk endometrial hyperplasia. The aim of this study was to investigate the efficacy of the low-dose levonorgestrel-impregnated intrauterine system (LNG-IUS) 13.5 mg (JaydessEndometrial carcinoma (EC) is presently the most frequent genital malignancy in women, showing a constant rise all over the Western world (1, 2). Endometrial hyperplasia, the preliminary stage of EC, undergoes malignant transformation in up to 29% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…However, ethical considerations prevented conservative management for these women as low-dose LNG-IUS had never before been explored as therapy for EHP. In the present study we hypothesized that hyperplastic foci within EP had the same risk of malignant progression as EH and that these hyperplastic foci would respond to progestin therapy in a similar manner as observed for nonpolypoid EH (10,17,26). Risk-stratification of EH by D-score analysis have been successfully used for years in our clinic and in a recent retrospective study with long-term follow-up, these methods were reported to be applicable as predictors of malignant transformation in EHP as well (15).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, ethical considerations prevented conservative management for these women as low-dose LNG-IUS had never before been explored as therapy for EHP. In the present study we hypothesized that hyperplastic foci within EP had the same risk of malignant progression as EH and that these hyperplastic foci would respond to progestin therapy in a similar manner as observed for nonpolypoid EH (10,17,26). Risk-stratification of EH by D-score analysis have been successfully used for years in our clinic and in a recent retrospective study with long-term follow-up, these methods were reported to be applicable as predictors of malignant transformation in EHP as well (15).…”
Section: Discussionmentioning
confidence: 92%
“…In a recent study, low-dose LNG-IUS (Jaydess ® , Bayer Pharmaceuticals, Berlin, Germany), with a total content of 13.5 mg levonorgestrel, was successfully given as therapy for six months in women with low-and medium-risk EH (17). Compared to the high-dose LNG-IUS, the thinner insertion tube and smaller T-frame might prove beneficial for young nulliparous women and for elderly women with stenotic cervical channel simultaneously reducing systemic side-effects to a minimum.…”
mentioning
confidence: 99%
“…All endometrial tissue specimens (baseline and post therapy biopsies) were conserved in RNAlater stabilization solution (Ambion RNAlater™, ThermoFisher Scientific, Whatham, MA, USA, code AM7021) and immediately frozen and kept at-18 °C until further analysis. Details of the clinical investigations are reported earlier [ 3 , 4 ] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The current data were a second gain of two clinical investigations [ 3 , 4 ] . The investigations were approved by the Regional Committees for Medical and Health Research Ethics (2015/381) and by the Norwegian Medicines Agency (EUDRACT nr 2015–000612- 17).…”
Section: Acknowledgmentmentioning
confidence: 99%
See 1 more Smart Citation